Incidence and determinants of hematotoxicity in acute lymphoblastic leukemia children who received 6-mercaptopurine based maintenance therapy in Addis Ababa, Ethiopia - Awol Mekonnen Ali; Haileyesus Adam; Daniel Hailu; Marieke J. H. Coenen; Rawleigh Howe; Teferra Abula (PLoS ONE, 2023)
Introduction The maintenance phase of acute lymphoblastic leukemia treatment is the final and longest stage of treatment, mainly focused on antimetabolite therapy. This phase is essential to eliminate residual leukemic clones and prevent relapse. However, dose-limiting hematotoxicity is a major problem during this phase resulting in dose reduction or treatment discontinuation. Objective In this cohort study, the clinical features and risk factors of hematological toxicity during the maintenance phase of treatment were analyzed in pediatric patients from Ethiopia. Methods A total of 160 patients from Tikur Anbessa specialized hospital were included in the study of which 142 had sufficient data available for analysis. Patient characteristics as well as information about the care-givers, sides-effects as reported by the care-givers and clinical factors were collected. Bivariable followed by multivariable analysis was performed to investigate which factors were associated with hematological toxicity during the maintenance phase. Results During the first six months of maintenance phase treatment grade 4 neutropenia was detected in 52.8% of the patients. The risk of developing grade 4 neutropenia was increased by about two fold in children with the age of 6 years and less compared to those with the age of more than 6 years. Similarly, the rate of developing grade 4 neutropenia among children with less than 4,500 maintenance day 1 white blood cell counts was significantly higher than that of children with normal maintenance day 1 white blood cell counts (AHR 2.477, 95% CI = 1.461–4.200, p = 0.001). Conclusion In conclusion, child’s age and day 1 maintenance white blood cell/absolute neutrophil counts significantly affected the occurrence of grade 4 hematotoxicity. Close monitoring for white blood cell and absolute neutrophil counts during maintenance phase treatment is recommended for early diagnosis of hematotoxicity.